Histopathological study of cystoscopic bladder biopsies - R Baidya; B Sigdel; NL Baidhya (Association of Clinical Pathologists of Nepal, 2015)
Background: Urinary bladder diseases constitute an important source of clinical signs and symptoms which are more disabling than lethal. The prevalence of bladder tumor in developed countries is approximately six times higher compared with that in developing countries. The aim of this study was to find out various lesions in urinary bladder biopsies and its frequencies. Materials and Methods: This was a five year retrospective study from January 2008 to December 2013, carried out at B&B Hospital, Lalitpur. All the relevant data of 324 patients who had undergone cystoscopic biopsy of urinary bladder were included in the study. All blocks were retrieved and stained with Hematoxylin and Eosin stain and examined under light microscope. Results: The spectrum of pathological lesions included inflammations and tumors. Non-neoplastic lesions were predominant (61.11%) followed by Transitional cell tumors accounted for 124 cases (38.27%). Non-neoplastic lesions comprises of cystitis and tuberculosis. Papillary urothelial neoplasms was the most common tumors seen in this study with 55 low grade, and 54 high grade Papillary urothelial carcinoma according to recent WHO grading. Single cases each of adenocarcinoma and paraganglioma were diagnosed. Conclusion: Cystoscopic biopsies help in the early diagnosis and treatment of various bladder lesions. Analysis of cystoscopic biopsies was done to ascertain the type of urinary bladder lesions in our country. Journal of Pathology of Nepal (2015) Vol. 5, 717-719